MEKANISMEN PASAR MODAL SYARIAH - Prasetyo, Totok Adhi (At-Tawazun, Jurnal Ekonomi Syariah, 2019)
A country's economic development cannot be separated from the capital market. The capital market functions as a means to mobilize public funds and to seek ownership of a company's shares by selling it. The Islamic capital market functions as an investment medium for Muslims in the capital market in line with Islamic principles. Some criteria for sharia capital market formation are to form a fair price, the existence of perfect information, free from usury, gharar, gambling and other transactions that conflict with sharia rules. Shares traded on the Islamic capital market must come from issuers that meet the criteria for sharia and bonds issued must use mudarabah, musyarakah, ijarah, istisna 'and salam. In this paper, the author will discuss the Islamic capital market and matters related to it. Matters raised in this discussion include the understanding of the Islamic capital market, its history, its functions, its laws, the actors involved in it, the types of capital markets, its instruments, how the Jakarta Islamic Index operates, how the mechanism of sharia capital markets operates, how determine stock prices, the characteristics of the capital market, how the Islamic fist against speculation, the constraints of developing the Islamic capital market and how the development strategy.